Recombinational junctions of variants of Moloney murine sarcoma virus: generation and divergence of a mammalian transforming gene. - Donoghue, D J (1983)
Different variants of Moloney murine sarcoma virus (MSV) were examined by nucleotide sequencing to compare the junctions between the acquired cellular sequence, v-mos, and the adjacent virus-derived sequences. These variants included 124-MSV, m1-MSV, and HT1-MSV and also the purportedly independent isolate Gazdar MSV. These four strains have an identical 5' junction between the murine leukemia virus env gene and the v-mos gene. This junction lies within the sixth codon of the chimeric env-mos coding region that encodes the transforming gene product. In contrast, at the 3' junction between the v-mos gene and the murine leukemia virus env gene, the three variants examined here were all different. A small deletion was found in the COOH-terminal portion of the m1-MSV env-mos coding region, indicating that the COOH terminus of this transforming gene product must be different from that of 124-MSV or HT1-MSV. The data presented here are consistent with the thesis that a virus closely related to HT1-MSV was the primordial Moloney MSV, and that all other related strains evolved from it by deletion or rearrangement. The variability observed in the Moloney MSV family is discussed in terms of possible mechanisms for the initial capture of mos sequences by the parental retrovirus and also in comparison with other transforming retrovirus families, such as Abelson murine leukemia virus and Rous sarcoma virus.